2016
DOI: 10.2174/1874123101610010004
|View full text |Cite
|
Sign up to set email alerts
|

Useful Bioactive Substances from Wastes: Recovery of Trans-Resveratrol from Grapevine Stems

Abstract: The methods for producing natural resveratrol are of big interest because of the many health benefits of this substance and its increasing use in functional foods, food supplements and para-pharmaceutical preparations. Generally, resveratrol is extracted from different natural sources, most of them usually produced for consumption purposes (grapes, nuts). This paper presents a method for recovery of resveratrol from a widely available raw material - grapevine stems, a by-product of vine pruning. An efficient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
(19 reference statements)
0
15
1
Order By: Relevance
“…They concluded that a higher ration of solvent to solid ratio, 5:1 is better for the extraction. The difference between the ratio obtained in this research, 3:1, and the one Angelov et al [29], 5:1, can be explained based on the water content of the biomass used for the extortion. Leaves used in the current study have a much higher water content than grapevine stems.…”
Section: Verification Of Experimentscontrasting
confidence: 78%
See 1 more Smart Citation
“…They concluded that a higher ration of solvent to solid ratio, 5:1 is better for the extraction. The difference between the ratio obtained in this research, 3:1, and the one Angelov et al [29], 5:1, can be explained based on the water content of the biomass used for the extortion. Leaves used in the current study have a much higher water content than grapevine stems.…”
Section: Verification Of Experimentscontrasting
confidence: 78%
“…Angelov et al [ 29 ] have studied the extraction of resveratrol from grapevine stems using a mixture of ethanol and water as the solvent [ 29 ]. They concluded that a higher ration of solvent to solid ratio, 5:1 is better for the extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Pinelo et al (2005) demonstrated that an increase of this ratio (expressed in milliters of solvent per gram of solid, mL.g -1 ) from 1 to 5 mL.g -1 could dramatically improve the extraction of phenolic compounds from grape pomace. Angelov et al (2016) also approved this low limit of 5 mL.g -1 as it is accurate for good wetting of grapevine stems and to extract total phenolic content (TPC expressed in milligrams of gallic acid equivalents per gram of grape canes, mg(GAE).g -1 ). The authors also studied TPC extraction from globe artichoke and rosehip while increasing solventto-solid ratio (Angelov et al, 2014(Angelov et al, , 2015.…”
Section: Solvent-to-solid Ratiomentioning
confidence: 99%
“…However, grapevine by-products are known to contain high-value molecules. 4,5 Among them, stilbenes are phenolic compounds having considerable importance for the grapevine since they defend the plant against aggressions from pathogenic microorganisms by acting as phytoalexins. 6 They are derived from the shikimicpolymalonic acid pathway and are biosynthesized by the combination of three malonyl CoA and one p-coumaroyl-CoA by stilbene synthase (StSy) to form trans-resveratrol, the first brick of stilbenoid compounds biosynthesis.…”
Section: Introductionmentioning
confidence: 99%